Energy-storage covalent organic frameworks: improving performance via engineering polysulfide chains on walls. Issue 23 (17th May 2019) - Xu, Fei; Yang, Shuhao; Chen, Xiong; Liu, Qianhui; Li, Hejun; Wang, Hongqiang; Wei, Bingqing; Jiang, Donglin
Abstract : The aligned one-dimensional channels found in covalent organic frameworks offer a unique space for energy storage. Abstract : The aligned one-dimensional channels found in covalent organic frameworks offer a unique space for energy storage. However, physical isolation of sulfur in the channels is not sufficient to prevent the shuttle of lithium-sulfide intermediates that eventually results in a poor performance of lithium–sulfur energy storage. Herein, we report a strategy based on imine-linked frameworks for addressing this shuttle issue by covalently engineering polysulfide chains on the pore walls. The imine linkages can trigger the polymerization of sulfur to form polysulfide chains and anchor them on the channel walls. The immobilized polysulfide chains suppress the shuttle effect and are highly redox active. This structural evolution induces multifold positive effects on energy storage and achieves improved capacity, sulfur accessibility, rate capability and cycle stability. Our results suggest a porous platform achieved by pore wall engineering for tackling key issues in energy storage.